VD_FINDINFO AI 193/08 - 440/2010 vom 9. November 2010 - VD Tribunal cantonal (2010)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, DEGRÉ DE L'INVALIDITÉ | 1 LAI, 28 LAI, 69 al. 1 let. a LAI, 69 al. 1bis LAI, 16 LPGA, 56 LPGA, 57 LPGA, 60 al. 1 LPGA, 61 let. b LPGA, 61 let. g LPGA, 117 al. 1 LPA-VD, 2 LPA-VD, 50 LPA-VD, 55 al. 1 LPA-VD, 91 LPA-VD, 93 al. 1 let. a LPA-VD, 99 LPA-VD